ANALYSIS OF OIL CONTENT SEAWATER AND DIATOMS ABUNDANCE IN COAST SAKERA WATERS OF BINTAN REGENCY OF RIAU ISLANDS PROVINCE - Abdullah '; Irvina Nurrachmi; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Coast Sakera of Bintan regency of Riau Islands province has become location implementation research On July 2016, with a goal determine the oil content and the abundance of diatoms in each station and the relationship between oil content with the abundance of diatoms. The survey method was applied in four stations, each station consists of three sampling points. Based on the result, the hinghest average value of oil content was obtained at station 3 (0,3587 ppm) and the lowest was at station 4 (0,1238 ppm). Diatoms were found in the surface waters of coast Sakera were 12 species. Where the species most dominating is Isthmia sp 2 Nitzschia sp 1 and Nitzschia sp 2. Based on the result, the hinghest average value of diatoms was obtained at station 4 (104 ind/l) and the lowest was at station 3 (51 ind/l). The relationship between oil content with diatom abundances has weak negative correlation, wich mean increasingly high of oil content will decline the abundance of diatoms of coast Sakera.Keywords : Coast Sakera, abundance, oil, and diatoms